Advances in computer forensics - Abdullah @ Selimun, Mohd Taufik; Mahmod, Ramlan; Abd Ghani, Abdul Azim; Abdullah, Mohd Zain; Md Sultan, Abu Bakar (2008)
Constant developments in information technology and communication have posed challenges for those policing cyber crimes. Due to the application of computer used to investigate computer-based crime has led to development of a new field called computer forensics. This paper discusses the research category in computer forensics and identifies key research issues of each of the category. Hopefully this paper would provide foundation and new ideas for the researcher to better understand the concepts of computer forensic. The outcome presents in this paper came from thoroughly review of recent computer forensic literatures.